22. PENGARUH UMUR LARVA IKAN NILA (Oreochromis niloticus) TERHADAP PENINGKATAN PENJANTANAN MENGGUNAKAN HORMON METHYL TESTOSTERONE (MT) ALAMI Effect of Tilapia (Oreochromis niloticus) Age in Masculinization Process Using Methyl Testosterone (MT) Natural Hormones - Rosmaidar R (Jurnal Medika Veterinaria, 2016)
This research aims to know the influence of larvae of nile tilapia (Oreochromis niloticus) age on masculinization process by the administration of methyl testosterone (MT) natural hormones. This research used 270 nile tilapia larvae divided into 3 age of groups: 5 days (PI), 10 days (PII), and 20 days (PIII), with three repetitions. Larvae were dipped in MT natural hormone for 20 days then reared until age of 60 days, followed by observations of fish sex. The average percentage of male-sex of tilapia fish after dipping with methyl testosterone natural hormone on group PI, PII, and PIII were 68.07%, 66.47%, and 57.29%, respectively. It can be concluded that the age of larvae do not affect the percentage of masculinization process of nile tilapia fish. ____________________________________________________________________________________________________________________ Key words: larvae tilapia, masculinization, methyl testosterone natural hormone